Avaliação da imunossupressão causada pela administração oral e subcutânea de dexametasona em ratos infectados experimentalmente por Strongyloides venezuelensis - Corrêa, Luisa Queiroz (2018)
Rodents infected with Strongyloides venezuelensis are experimental models applied to strongyloidiasis study. This work evaluated and compared the efficacy of two routes of dexamethasone (DEX) administration for induction of immunosuppression a model in murine strongyloidiasis. Rattus norvegicus Wistar were divided into groups of six animals each: G I: untreated and uninfected animals; G II: untreated and infected animals; G III: animals treated by oral administration and uninfected; G IV: animals treated by oral administration and infected; G V: animals treated by subcutaneous administration and uninfected; G VI: animals treated by subcutaneous administration and infected. For oral treatment, DEX was diluted in sterilized water (5 μl/ml) and made available to the animals for 5 days (-5 to 0, 8 to 13, and 21 to 26). For the subcutaneous treatment animals received DEX disodium phosphate (2 mg/kg) daily injections. The infection was established by 3000 S. venezuelensis filarioid larvae subcutaneous inoculation per animal. The groups were evaluated by physical (body weight), hematological (global and differential leukocytes count), immunological (IgG, IgG1 and IgG2a detection) and parasitological parameters (egg count per gram of feces and parasite females). The groups treated with DEX, especially by the subcutaneous route, presented difficulty to gain weight throughout the days. On the 8th, 13th, 21st and 30th days post infection (d.p.i.), the global leukocyte count of GIII, G IV, G V and G VI was low compared to G I and G II controls. On the same days a decrease in the number of lymphocytes and an increase in the number of neutrophils in the immunosuppressed groups were observed, in a way that was reversed to the controls. The IgG, IgG1 and IgG2a levels for all groups, except for positive control G II, were below the detection threshold. G IV was the group that eliminated eggs the most, with occurrence of elimination peaks on 13th and 26th d.p.i The numbers of eggs eliminated by G VI were similar to those found for control (G II) on days 5, 7, 8, 13 and 21, and higher on days 26 and 30.The parasitic females recovery at 30th d.p.i.. was significantly higher in G IV. Both treatments led to the suppression of aspects related to the cellular and humoral immune response, but the treatment by the oral route showed to be effective in increasing the parasitic load. Pharmacological immunosuppression induced by the oral route of DEX produces a high parasitic load, is safe and non-invasive, and consists in a useful protocol for the strongyloidiasis immunobiological aspects study.